2000
DOI: 10.1074/jbc.m005040200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Nucleotide Regulation of Na+/Glucose Cotransporter (SGLT1) mRNA Stability

Abstract: Expression of the Na؉ -coupled glucose cotransporter SGLT1 is regulated post-transcriptionally at the level of mRNA stability. We have previously demonstrated that cAMP-dependent stabilization of the SGLT1 message was correlated with the protein phosphorylationdependent binding of cytoplasmic proteins to a uridinerich sequence (URE) in the 3-untranslated region (UTR). In the present study, the regulatory role of the URE was demonstrated by inserting it into the 3-UTR of a ␤-globin reporter minigene under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…The proteins in these labeled bands are slightly smaller than these sizes because each species contains crosslinked RNA. The 40-kDa species is the size expected for labeled HuR, consistent with results obtained by others (24,25). It is interesting that this species is present at similar levels in nuclear and cytoplasmic extracts, even though HuR is present at much higher levels in nuclear fractions (Fig.…”
Section: Fig 4 the Cytoplasmic Localization Of Hur Is Regulated By supporting
confidence: 80%
See 1 more Smart Citation
“…The proteins in these labeled bands are slightly smaller than these sizes because each species contains crosslinked RNA. The 40-kDa species is the size expected for labeled HuR, consistent with results obtained by others (24,25). It is interesting that this species is present at similar levels in nuclear and cytoplasmic extracts, even though HuR is present at much higher levels in nuclear fractions (Fig.…”
Section: Fig 4 the Cytoplasmic Localization Of Hur Is Regulated By supporting
confidence: 80%
“…It is possible that covalent modification of HuR or another protein in the complex could affect the specificity or affinity of one of the proteins. In fact, it has been shown that cAMP stimulates the formation of a HuR-containing complex on the SGLT1 mRNA by a mechanism that involves protein phosphorylation (24,25,28). In addition, it is possible that amino acid starvation causes changes in the levels of another protein that binds to the cat-1 mRNA along with HuR.…”
Section: Fig 4 the Cytoplasmic Localization Of Hur Is Regulated By mentioning
confidence: 99%
“…They identified a correlation between the increase of SGLT1 mRNA during confluence with an increase of the intracellular cAMP and showed that SGLT1 mRNA was increased by cAMP-elevating agents (22). Furthermore, it was revealed that the cAMP-dependent increase of SGLT1 mRNA relied on a decelerated message degradation that was mediated by binding of a cytosolic protein to a defined 3Ј region of mRNA (21,25). In addition, it was found that the decrease of SGLT1 mRNA during de-differentiation can be blocked or accelerated by inhibition or stimulation of protein kinase C, respectively (19).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the transcriptional regulation of SGLT1 is known to occur more slowly. The expression of SGLT1 is altered via changes of intracellular mRNA concentrations that were reported to be mediated by factors either directly affecting the transcription (11) or the stability of the mRNA (21,25). When LLC-PK 1 cells grown in 5 mM Dglucose differentiate during confluence, the cytosolic concentration of SGLT1 mRNA increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation